The Effects of Information Communication Technologies on Human Capital: A Panel Data Analysis - Zeynep Erdinç; Gökçen Aydınbaş (Journal of Economy Culture and Society)
The transition to the information age with globalization has opened the doors of digital transformation all over the world. In this digital transformation process, each new day corresponds to new information. In addition, the dimensions of communication have started to change with new information. It has become inevitable that such developments in information and communication technologies will have an impact on human development. In this context, the effect of information and communication technologies on human capital in the academic field arouses curiosity. This study aims to investigate the effects of information and communication technologies on human capital with the panel data analysis method. Annual data based on the 2000-2019 period for 10 countries selected among the emerging economies were used in the study. The dependent variable was the human capital index; the control variables were the education index and life expectancy at birth, and the independent variable was the share of information and communication technologies exports in total exports in the study. According to the findings of the study, it was concluded that the share of information and communication technologies exports in total exports increased human capital along with the education index and life expectancy at birth.